Rapid team deployment : building high-performance project teams - Pokras, Sandy (Crisp Pub. Menlo ParkUS, 1995)
Focuses on teams assembled for specific periods to work on specific projects, and presents practical ways to launch and build them into successful high performance units. Identifies 13 characteristics of a high performance team. Explains how to cultivate these characteristics and use them to measure the team's performance level. Includes information on empowerment; team recruitment and charter; defining team requirements; establishing team leadership; and, ground rules.